The war in Croatia and Bosnia-Herzegovina, 1991-1995 - Magaš, Branka; Žanić, Ivo, 1954-; Malcolm, Noel, 1956- (Frank Cass, 2001)
This work provides an understanding of the wars in Croatia and Bosnia-Herzegovina. These two interdependent wars were the greatest armed conflicts in Europe in the second half of the 20th century. This work provides an analysis of their successes and failures.